Digital Dentistry in Contemporary Oral Healthcare: Innovations, Challenges and Prospects - Mai Almarzouki (Advances in Human Biology, 2026)
Abstract Digital dentistry is transforming oral healthcare by replacing traditional mechanical workflows with integrated, technology-based approaches. Initially limited to computer-aided design and manufacturing (CAD/CAM), it now includes a wide range of applications such as advanced imaging, diagnostics, orthodontics, implantology, prosthodontics and oral pathology. This review outlines the historical progression and current scope of digital dentistry, focusing on its ability to improve diagnostic accuracy, treatment efficiency and patient outcomes. Technologies such as intraoral scanners, 3D printing, artificial intelligence and virtual simulation tools have reshaped clinical workflows and offer evidence-backed advantages across specialities. However, challenges remain. High equipment and software costs, limited interoperability due to proprietary formats, data privacy concerns and a lack of standardised digital training continue to hinder widespread adoption, especially in low- and middle-income regions. The review identifies practical strategies to address these issues, including structured training programs, stronger data protection policies and mobile digital units to improve rural access. Public–private partnerships and updated academic curricula can also support broader integration. Comparative tables help clarify the strengths and limitations of key innovations. As newer tools such as robotics, bioprinting and predictive analytics emerge, digital dentistry is set to play an increasingly central role in modern, patient-centered dental care.